Prevalence and Risk Factors for Development of Venous Thromboembolism After Degenerative Spinal Surgery. Issue 5 (1st March 2015) - Yoshioka, Katsuhito; Murakami, Hideki; Demura, Satoru; Kato, Satoshi; Tsuchiya, Hiroyuki
Abstract : Study Design: Prospective clinical study. Objective: To identify the incidence and risk factors for venous thromboembolism (VTE) associated with degenerative spinal surgery procedures at the different spinal levels for various pathologies. Summary of Background Data: Spinal surgery includes procedures for treatment of various pathologies at different spinal levels. There have been no studies on VTE after degenerative spinal surgery with respect to screening patients for both deep venous thrombosis and pulmonary thromboembolism (PE). Methods: We prospectively investigated the occurrence of VTE after degenerative spinal surgery in 459 patients who were divided into 5 groups: group 1, patients with cervical degenerative disease treated with posterior decompression; group 2, patients with cervical degenerative disease treated with instrumentation for spinal fusion; group 3, patients with thoracolumbar degenerative disease treated with instrumentation for spinal fusion; group 4, patients with lumbar spinal stenosis treated with posterior decompression; and group 5, patients with lumbar spondylolisthesis treated with 1-level posterior lumbar interbody fusion. A deep venous thrombosis and PE screening was performed for all patients. Binomial logistic regression analysis was used to assess the association of risk factors. Results: The incidence of VTE was 2.8%, 3.4%, 10.8%, 12.5%, and 10.1% in groups 1, 2, 3, 4, and 5, respectively. Female sex, advanced age, spinal level, and neurological deficits, were all risk factors. Cervical spinal surgery in particular had an associated low risk. In patients with PE, 3 of the 4 had no deep venous thrombosis, indicating that screening for PE is also needed in high-risk patients. Conclusion: The prevalence of VTE after elective spinal surgery was different in each group. Level of Evidence: 3 Abstract : We evaluated the incidence and risk factors for venous thromboembolism associated with degenerative spinal surgery procedures at the different spinal levels for various pathologies. Although female sex, advanced age, spinal level, and neurological deficits, were all risk factors, cervical spinal surgery in particular had an associated low risk.